Protein Lipidation - Tamanoi, Fuyuhiko; Sigman, D. S. (Enzymes, 2001)
This is the first compilation of protein lipidation enzymes. This volume summarizes recent dramatic developments regarding enzymes responsible for protein lipidation, a process critical for a number of physiological functions, including cell proliferation and morphology. Inhibitors of protein lipidation have recently been shown to be useful as anticancer drugs. Enzymatic mechanisms, mutational analysis, and structural studies are presented. Key Features * The enzymatic mechanisms of protein lipidation * Three-dimensional structures of protein farnesytransferase, protein geranylgeranytransferase II, and n-myristoryltransferase.